GABAB Receptor - Colombo, Giancarlo (The Receptors, 2016)
An up-to-date comprehensive overview of the GABA B receptor system with a particular focus on the most recent therapeutic applications and potential. This receptor system has recently been implicated in several diseases and disorders including gastroesophageal reflux disease, epilepsy, mood disorders, depression, and alcohol and substance use disorder. The authors, leading researchers in the field, explore a number of approaches, including medicinal chemistry, molecular biology, physiology, and preclinical and clinical pharmacology. This overview provides a translational perspective on the potential of the GABA B receptor pharmacology.